Necrotizing gingivitis in patients with and without HIV: a systematic literature review and meta-analysis - Bianca Carla de Souza Lorentz; Lara Fábia da Costa Guimarães; Sâmila Gonçalves Barra; Camila Batista da Silva de Araujo Candido; Daniel Felipe Fernandes Paiva (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Necrotizing periodontal diseases are historically established conditions that gained prominence during the First World War. Their etiology was linked to poor oral hygiene, opportunistic infections, and stress. Characterized by severity and debilitation, the disease progresses rapidly with necrotic ulcers in periodontal tissues, resulting in pain, tissue bleeding, and a foul odor. Due to the distinctive features and accelerated evolution of periodontal conditions in immunocompromised patients, individuals with Human Immunodeficiency Virus leading to Acquired Immunodeficiency Syndrome are classified as at-risk patients for the development of Necrotizing periodontal diseases. Thus, this review aims to compare the prevalence of gingivitis and necrotizing periodontitis in AIDS patients in comparison to the immunocompetent population. Additionally, it seeks to evaluate how the state of immunosuppression alters the oral cavity and provides clarity regarding the impact of AIDS on periodontal diseases. This study adhered to the methodological protocols of a systematic review as outlined in the Cochrane Handbook. The search strategy was implemented across the following databases: Pubmed, Cochrane Library, Scopus, Web of Science, and Embase. The association of necrotizing periodontal diseases in HIV+ individuals was investigated through a systematic analysis of the literature.